1980
DOI: 10.1159/000153147
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1-Antitrypsin Types and Chronic Obstructive Lung Disease in an Industrial Community in Northern Sweden

Abstract: In a community in Västerbotten county in northern Sweden occupationally dominated by a sulphite pulp factory all individuals (n = 3,466) received a questionnaire concerning respiratory symptoms, 94.0% answered and 8.1% claimed to have symptoms indicative of chronic obstructive lung disease (COLD). Of these individuals 93% were examined clinically, and the relationships between respiratory symptoms, verified COLD, smoking, occupation and quantitative and qualitative variations in the α1-antitrypsin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 4 publications
3
14
0
Order By: Relevance
“…However, our results indicate that this difference is due to smoking habits and occupational exposure at the Horne fors factories and not to rare Pi types. Thus, the present results indicate that indi viduals heterozygous for the MZ, MS and MF types do not have an increased risk for CB, a result which is in accordance with some reports [6,15,16] but not with others [5,17].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, our results indicate that this difference is due to smoking habits and occupational exposure at the Horne fors factories and not to rare Pi types. Thus, the present results indicate that indi viduals heterozygous for the MZ, MS and MF types do not have an increased risk for CB, a result which is in accordance with some reports [6,15,16] but not with others [5,17].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study we were not able to show such an effect among individuals occupa tionally exposed to SOi or chlorine, nor was the serum level significantly increased in smokers compared to non-smokers. Low cq-AT serum levels in M type indi viduals were not associated with respirato ry disease in the present and in an earlier study of the Hornefors community [17], As in an earlier study [19] we have found a quantitative difference in serum levels between heterozygotes (M|Mi) and (M i + Mi) homozygotes.…”
Section: Discussionsupporting
confidence: 81%
“…To account for environmental exposures, some population-based cross-sectional studies compared MZ to MM groups among industry workers [18,61,75]. Some of the studies that found an increased frequency of MZ genotypes in industry workers with COPD lacked matching for age and smoking [61,76]. HORNE et al [18] compared MZ and MM grain workers and matched for age, years of employment and smoking.…”
Section: Effects Of Environmental and Occupational Exposuresmentioning
confidence: 99%
“…In some of these studies it seemed that a deficit in c~l Pi tended to reveal or to increase the risk of p u l m o n a r y impairment related to occupational exposures. Beckman (2) found that bronchitis was related to SO2, C12 and smoking habits in subjects with phenotypes MS, MZ, FM, Z. Rosehall ,(16) also found that chronic bronchitis tended to be more frequent among such ~l Pi deficient subjects exposed to SO2 and Clv Tattersall (.17) also reported that alveolar abnormalities without bronchial abnormalities tended to be more frequently observed in MZ subjects. Pulmonary s y m p t o m s were more frequently observed by Chan Yeung et al (6) among non-smokers with phenotype MS, but this author considers that heterozygotism is not a noticeable risk factor in association with low levels of exposure to wood or grain dusts.…”
Section: T a B L E 8 --L U N G F U N C T I O N Tests: C H A N G E S mentioning
confidence: 95%